2014
DOI: 10.1021/la501922u
|View full text |Cite
|
Sign up to set email alerts
|

QCM-Based Measurement of Chlorine-Induced Polymer Degradation Kinetics

Abstract: Highly structured network polymers are prepared via a molecular layer by layer technique (mLbL) and used as a model system to study aqueous degradation of polymer thin films in real time. Quantitative analysis of the degradation kinetics was enabled by the use of a quartz crystal microbalance (QCM). We conclude that the common metric of halogen, specifically chlorine, exposure (concentration × time) to be an ineffective normalization unit and showed a multistage adsorption process consistent with the establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Gypsum scaling kinetics for the TMC-and MPD-terminated polyamide films were studied using a quartz crystal microbalance (QCM, E-4 model, Q-Sense Inc., Biolin Scientific, Linthicum Heights, MD), which measures changes in the resonance frequency of a QCM sensor over time as it is exposed to a gypsum scaling solution. The changes in frequency (Δf) at the third overtone were related to accumulated gypsum mass (Δm) on the sensor via the Sauerbrey relationship [31]: (2) where C = 17.7 ng cm -2 s -1 for AT-cut quartz QCM sensor, and n is the overtone of fundamental resonance frequency (n=3).…”
Section: Quartz Crystal Microbalance (Qcm) Measurements Of Scaling Kimentioning
confidence: 99%
“…Gypsum scaling kinetics for the TMC-and MPD-terminated polyamide films were studied using a quartz crystal microbalance (QCM, E-4 model, Q-Sense Inc., Biolin Scientific, Linthicum Heights, MD), which measures changes in the resonance frequency of a QCM sensor over time as it is exposed to a gypsum scaling solution. The changes in frequency (Δf) at the third overtone were related to accumulated gypsum mass (Δm) on the sensor via the Sauerbrey relationship [31]: (2) where C = 17.7 ng cm -2 s -1 for AT-cut quartz QCM sensor, and n is the overtone of fundamental resonance frequency (n=3).…”
Section: Quartz Crystal Microbalance (Qcm) Measurements Of Scaling Kimentioning
confidence: 99%
“…Also, the changes observed for the peak around 1720 cm −1 can be correlated with the quick chlorination of the polyamide ending groups, as reported previously 19 . The chlorination mechanism involves an Orton rearrangement followed by hydrolysis of the amide bond, as it has been discussed abundantly as a potential degradation mechanism of PA by chlorine 7 , 12 . In addition, the MWCNT-PA samples exhibit a more stable structure against chlorine degradation, and the peaks intensity scarcely changed when the MWCNT content was 20 wt.%.…”
Section: Resultsmentioning
confidence: 99%
“…The latest research indicates that the degradation process is mainly due to the amide bond scission, produced after the chlorination of the nitrogen at the amide link 9 , 11 . In fact, the complete process is divided into two phases 12 : chlorine uptake, strongly depending on the free chlorine concentration, and a subsequent amide bond scission facilitated by the presence of hydroxyl ions (OH − ). The incorporation of low amounts of carbon nanomaterials such as CNT or graphene to the composite membranes has been already proposed as an alternative for increasing their resistance to chlorine degradation 2 , 3 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, viscoelastic properties of thin films originating from solvent-based swelling, conformational changes, and/or degradation processes can be captured. For example, QCM-D has been employed extensively to investigate the enzymatic degradation of polymers such as cellulose, , proteins, polyesters, and nanogels . QCM-D has also been used to understand polyamide membrane–foulant interaction mechanisms. To date, only one study utilized this technique to investigate the oxidant-induced polyamide degradation, which focused on the conventional disinfectant-free chlorine. The study showed that the polyamide film experienced an initial mass gain attributable to chlorine sorption and a subsequent mass loss attributable to film disintegration .…”
Section: Introductionmentioning
confidence: 99%
“…QCM-D has also been used to understand polyamide membrane–foulant interaction mechanisms. To date, only one study utilized this technique to investigate the oxidant-induced polyamide degradation, which focused on the conventional disinfectant-free chlorine. The study showed that the polyamide film experienced an initial mass gain attributable to chlorine sorption and a subsequent mass loss attributable to film disintegration . A similar technique is expected to provide molecular insight into PAA–polyamide interactions.…”
Section: Introductionmentioning
confidence: 99%